2005
DOI: 10.1074/jbc.m414489200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Mycobacterium tuberculosis D-3-Phosphoglycerate Dehydrogenase

Abstract: Phosphoglycerate dehydrogenases exist in at least three different structural motifs. The first D-3-phosphoglycerate dehydrogenase structure to be determined was from Escherichia coli and is a tetramer composed of identical subunits that contain three discernable structural domains. The crystal structure of D-3-phosphoglycerate dehydrogenase from Mycobacterium tuberculosis has been determined at 2.3 Å. This enzyme represents a second structural motif of the D-3-phosphoglycerate dehydrogenase family, one that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 32 publications
2
75
0
Order By: Relevance
“…However, the M. tuberculosis enzyme does not display the affinity for 5Ј-AMP-Sepharose that the rat liver and E. coli enzyme do, although all three utilize NAD as a cofactor. A possible reason for this is addressed in the accompanying article (21), which describes the crystal structure of M. tuberculosis PGDH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the M. tuberculosis enzyme does not display the affinity for 5Ј-AMP-Sepharose that the rat liver and E. coli enzyme do, although all three utilize NAD as a cofactor. A possible reason for this is addressed in the accompanying article (21), which describes the crystal structure of M. tuberculosis PGDH.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of M. tuberculosis PGDH does not reveal the site for chloride binding. A potential site for the binding of anionic molecules has been identified by virtue of the binding of tartrate molecules from the crystallization buffer at a site between the intervening and regulatory domains (21). However, tartrate itself does not exhibit an effect on the cooperativity of inhibition by serine.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoserine aminotransferase (PSAT), a PLP (pyridoxal-5Ј-phosphate)-dependent enzyme converts 3-phosphohydroxy pyruvate to O-phospho-L-serine that is subsequently dephosphorylated by phosphoserine phosphatase (PSP) into L-serine (11). Both 3-phosphoglycerate dehydrogenase and PSAT homologs in M. tuberculosis have been extensively biochemically characterized, and their crystal structures have also been determined (12)(13)(14). In a recent study, it has been shown that intracellular cyclic AMP regulates the levels of PSAT enzyme, and extracellular addition of L-serine restores the growth defect of M. tuberculosis crp mutant in vitro (15).…”
Section: Tuberculosis (Tb)mentioning
confidence: 99%
“…1A and Table 2). M. tuberculosis PGDH and PSAT enzymes catalyzing the first two steps of L-serine biosynthesis have been biochemically well characterized (13)(14)(15). Phylogenetic analysis among PSP proteins from various organisms revealed that PSP proteins from actinobacter and helicobacter species were more similar to each other in comparison with enterobacterial and human PSP enzymes (Fig.…”
Section: Bioinformatic and Homology Modeling Studies-mentioning
confidence: 99%
“…These structurally related ferredoxin-like fold proteins mediate allosteric regulation and ligand binding and typically undergo oligomerization through different strat- egies resulting in different oligomer architectures (14), in some cases similar to that presented by the peptidase M20/M25/M40 family ( Fig. 4B) (15,22). It has also been demonstrated that the sequence divergence of SMBDs such as ACT can expand beyond the detection limits of the sequence-based algorithm of PSI-BLAST (17), which would explain why this is the first time that the ACT-like nature of the dimerization domain of the peptidase M20/M25/M40 family has been found.…”
Section: R369 H219(a) N260(a)mentioning
confidence: 99%